Complex aortic procedure and cerebral protection strategies: a case report and review of the literature. Issue 2 (8th August 2015) - Tan, Jerry; Kothandan, Harikrishnan; Lee, Say Kiat
Summary: The increasing complexity of aortic procedures necessitates a team approach to maintain the integrity of end‐organ perfusion. The case report described here illustrates a complex hybrid aortic procedure in a patient who had had previous cardiac surgery. The patient underwent total aortic arch repair using an elephant trunk and thoracic endovascular aortic repair (TEVAR). Deep hypothermic circulatory arrest and bilateral selective antegrade cerebral perfusion was employed with adjunctive pharmacotherapy using sodium thiopental and methylprednisolone. We explore the current evidence base for the anaesthetic management of such complex aortic procedures as well as various cerebral protection strategies and their limitations.